Learning agile : understanding Scrum, XP, Lean, and Kanban - Stellman, Andrew; Greene, Jennifer, 1971- (O'Reilly, 2014)
Learning Agile is a comprehensive guide to the most popular agile methods, written in a light and engaging style that makes it easy for you to learn. Agile has revolutionized the way teams approach software development, but with dozens of agile methodologies to choose from, the decision to ""go agile"" can be tricky. This practical book helps you sort it out, first by grounding you in agile's underlying principles, then by describing four specific-and well-used-agile methods: Scrum, extreme programming (XP), Lean, and Kanban. Each method focuses on a different area of development, but they